9 = 5 - y/3

3 answers

To solve for y, we can start by isolating y on one side of the equation.

9 = 5 - y/3

Let's first get rid of the fraction by multiplying both sides of the equation by 3:

3 * 9 = 3 * (5 - y/3)

27 = 15 - y

Next, let's isolate y by subtracting 15 from both sides of the equation:

27 - 15 = 15 - y - 15

12 = -y

Finally, let's multiply both sides of the equation by -1 to solve for y:

-1 * 12 = -1 * -y

-12 = y

Therefore, the solution is y = -12.
My choice of order of operations is often not the same as that of the robots
9 = 5 - y/3
4 = -y/3
12 = -y
y = -12
Apologies for any confusion caused earlier. Your solution is correct. The solution to the equation 9 = 5 - y/3 is indeed y = -12.